Effect of deproteinized bovine bone matrix coverage on the resorption of iliac cortico-spongeous bone grafts - a prospective study of two cohorts - Wiltfang, Joerg; Jaetschmann, Nadine; Hedderich, Juergen; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Gierloff, Matthias (Clinical Oral Implants Research, 2014)
The augmentation of the alveolar ridge using iliac cortico-spongeous bone grafts is routinely used. However, bone grafts show a substantial degree of resorption, which may negatively affect the long-term success of dental implants in the augmented area. The aim of this study was to evaluate the effect of a deproteinized bovine bone matrix coverage on the resorption of iliac bone grafts.Two cohorts consisting of 40 patients who received a vertical augmentation of the alveolar ridge with onlay grafts from the iliac crest were prospectively investigated over a period of 2 years. In half of the patients (n = 40), the grafts were covered by a thin layer of deproteinized bovine bone matrix (DBBM cohort). The other 40 patients received the identical surgical procedure without a DBBM coverage (non-DBBM cohort). The graft height/resorption was radiographically determined immediately after surgery, 6 months, 1 year, and 2 years postoperatively.The height of the bone graft 6 months after surgery accounted 92.15% of the initial value in the DBBM cohort and 87.76% in the non-DBBM cohort. One year after augmentation, the height reduced to 83.95% in the DBBM cohort and 72.92% in the non-DBBM cohort. Two years after surgery, the resorption slowed down and the height of the grafts accounted 81.27% in the DBBM cohort and 71.43% in the non-DBBM cohort. The difference was statistically significant.Deproteinized bovine bone matrix reduces the postoperative resorption of iliac bone block grafts and may therefore enhance the long-term implant prognosis in the augmented area.
EVALuna2:24346